The complete larval development of Pagurus lanuginosus De Haan, 1849 (Decapoda, Anomura, Paguridae) reared in the laboratory, with emphasis on the post-larval stage - Sultana, Zakea; Asakura, Akira (Zootaxa, 2015)
The complete larval development of Pagurus lanuginosus is described and illustrated including the first description of the post-larval stage. Specimens were reared in the laboratory at 15°C and 33.5–35.02 PSU. Newly hatched larvae passed through a short prezoeal stage (10 minutes to 2 hours), four zoeal stages (6, 6, 6, 8 days), and one megalopal stage (10 days). We compared the morphological features of each larval stage with those of the preceding two descriptions on the same species, and found many differences in morphology and the duration between zoeal stages. We concluded that significant diagnostic characters separating this species from other congeners in Japanese waters include the presence of two pairs of yellowish chromatophores on the carapace in the zoeal stages, a translucent body flecked with red chromatophores, and two pairs of red chromatophores on the carapace in the megalopal stage.